Studi Pengaruh Personal Selling dan Digital Marketing terhadap Tingkat Kepuasan Nasabah di PT. Bank Mandiri Taspen KCP Parepare - Sulo, Rail; Putra, Pandi; Darmawansah, Darmawansah; Tijjang, Bakhtiar; Ali, Syahban Mada (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This research aimed to determine Personal Selling and Digital Marketing partially influence Customer Satisfaction at PT. Bank Mandiri Taspen KCP Parepare. To find out how personal selling and digital marketing simultan eously influence customer satisfaction at PT. Bank Mandiri Taspen KCP Parepare.The analysis method used is quantitative descriptive, using primary data sourced from the results of questionnaires that have been answered by respondents. The tests used include Validity Test, Reliability Test, Descriptive Analysis, Multiple Linear Regression Analysis and t Test (partial), f Test (simultaneous), R2 Test (Coefficient of Determinated).These results indicated that both Personal Selling and Digital Marketing have a partial effect on Customer Satisfaction at PT. Bank Mandiri Taspen KCP Parepare. simultaneously Personal Selling and Digital Marketing influence Customer Satisfaction at PT. Bank Mandiri Taspen KCP Parepare.